The study in the relationship between leadership traits and employee work performance at UiTM Jengka, Pahang: a case study / Nurul Hazwani Jamaludin, Norizan Mohamad Idzhar and Nurul Zunorain Jaafar - Jamaludin, Nurul Hazwani; Mohamad Idzhar, Norizan; Jaafar, Nurul Zunorain (2012)
In this new era of globalization, organizations everywhere whether in the private or even in the public sector always try to improve the employees performance in order to achieve organizational goals. Thus, many alternatives had been implemented by the organizations in order to improve the employee's performance such as provided their staff with motivational based-seminars. The organization itself provided training programs as well in order to help the employees understand the organization goals better and at the same time, improved the relationship with the customers. The organization also used rewards (in form of payment and career opportunities to induce employees to use more of their inputs (e.g. time effort, experience, skills, creativity, knowledge, and job behaviors) in order to increase employee's productivity (Abubakr M. Sulaiman, et al. 2010). There was a positive relationship between job performance and the status of the talent itself according to Greenberg and Baron, (2000). This positive relationship bring on by the perks and benefits normally standing occupational such as higher payment a more flexible working condition which was less dependent on physical labour. The employee's personality view as the empirical literature on the relationship between personality traits and job performance had shown that it was an important determinant of employee's job performance (Abubakr M.Sulaiman, et al. 2010)